2013
DOI: 10.1161/circulationaha.112.118463
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Statewide Pre-Hospital STEMI Strategy to Bypass Hospitals Without Percutaneous Coronary Intervention Capability on Treatment Times

Abstract: Background— The ultimate treatment goal for ST-segment elevation myocardial infarction (STEMI) is rapid reperfusion via primary percutaneous intervention (PCI). North Carolina has adopted a statewide STEMI referral strategy that advises paramedics to bypass local hospitals and transport STEMI patients directly to a PCI-capable hospital, even if a non-PCI-capable hospital is closer. Methods and Results— We assessed the adherence of emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 29 publications
6
88
0
2
Order By: Relevance
“…These improvements were not seen for transfer‐in patients. Although PCI‐capable hospitals in recent years have increased in numbers by almost 50%, and 90% of Americans currently live within 60 minutes of a PCI‐capable facility,17, 18, 19, 20 45% of the patients treated with primary PCI were still not treated within the guideline‐recommended goals, in line with previous reports 5, 11, 12. Even though improvement may have continued to occur beyond the study measurement period, it is still highly likely that further efforts will be needed to maintain and improve quality of the regional efforts seen in this study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These improvements were not seen for transfer‐in patients. Although PCI‐capable hospitals in recent years have increased in numbers by almost 50%, and 90% of Americans currently live within 60 minutes of a PCI‐capable facility,17, 18, 19, 20 45% of the patients treated with primary PCI were still not treated within the guideline‐recommended goals, in line with previous reports 5, 11, 12. Even though improvement may have continued to occur beyond the study measurement period, it is still highly likely that further efforts will be needed to maintain and improve quality of the regional efforts seen in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Despite decades of evidence, including randomized trial data calling for primary PCI within FMC2D times of ≤90 minutes for direct EMS‐transported cases and ≤120 minutes for patients requiring interhospital transfer, up to 30% to 50% of all patients with STEMI are not treated within these guideline‐recommended goals for timely reperfusion 5, 10, 11, 12, 13, 14. Previous studies have shown that patients with STEMI with OHCA constitute an important subgroup, with significantly higher rates of system delay and mortality relative to patients with STEMI without OHCA 1.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid reperfusion by primary percutaneous coronary intervention (PCI) is the preferred strategy for treating patients with ST-segment elevation myocardial infarction (STEMI) [1]. Guidelines recommend that reperfusion therapy with primary PCI should be administered as soon as possible to all eligible patients with STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that pre-hospital electrocardiographic diagnosis and direct referral to PCI-capable hospitals decrease the time delay in treating patients with STEMI [1,8,9]. Quality improvement strategies have reduced door-to-balloon times for direct-arrival patients with STEMI undergoing primary PCI.…”
Section: Introductionmentioning
confidence: 99%
“…The patients who had no ST change were transferred to other hospitals without PCI capability. 25) They may have needed a gastroscopy exam later on. This Doctor Car with a mobile cloud ECG system contributed to the effective and economical use of regional medical resources.…”
Section: Discussionmentioning
confidence: 99%